2013
DOI: 10.2174/1566523211313020003
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells or Induced Pluripotent Stem Cells? A DNA Integrity Perspective

Abstract: Induced pluripotent stem cells (iPSCs) and embryonic stem cells (ESCs) are two types of pluripotent stem cells that hold great promise for biomedical research and medical applications. iPSCs were initially favorably compared to ESCs. This view was first based on ethical arguments (the generation of iPSCs does not require the destruction of an embryo) and on immunological reasons (it is easier to derive patient HLA-matched iPSCs than ESCs). However, several reports suggest that iPSCs might be characterized by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 62 publications
0
30
0
2
Order By: Relevance
“…Embryonic stem cells (ESCs) have greater therapeutic potential than iPSCs because they have fewer genetic and epigenetic defects [41]. Porcine SCNT is also a promising technology, with potential applications in regenerative medicine and xenotransplantation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic stem cells (ESCs) have greater therapeutic potential than iPSCs because they have fewer genetic and epigenetic defects [41]. Porcine SCNT is also a promising technology, with potential applications in regenerative medicine and xenotransplantation [2].…”
Section: Discussionmentioning
confidence: 99%
“…However, before clinical implementation of induced PSCs transplantation there is required to perform fundamental investigations related the specificity, efficiency, kinetics, and biological safety of novel methods of cell reprogramming. Despite results of controlled studies in this field are limited, novel approaches regarding improve and change the induced PSC process promise to be more successful than previous [31] . Currently there are some transcription factors (molecular factors, vectors, various small molecules) that might be useful for improving functionality of induced PSCs before replacement.…”
Section: Results Of Pre-clinical Studies Of Stem Cell-based Therapymentioning
confidence: 99%
“…Results of the recently studies have been found that using transcription factors for trans-differentiation of induced PSC into patient-specific cells may open a new era of regenerative medicine. The use of different types of somatic cells with trans-differentiation technology is consider an important approach for improving plastic of induced PSC reprogramming and as serious extend of possibilities for increasing efficacy and biological safety of regenerative medicine [29,31] . Finally, irrespective several limitation of clinically-based evidences of implementation of transdifferentiation on routine clinical practice, it is required to accumulate efforts toward summarize of knowledge about novel method of induced PSC transcription.…”
Section: Results Of Pre-clinical Studies Of Stem Cell-based Therapymentioning
confidence: 99%
“…The reason for differences in the types of karyotypic abnormalities in iPSC versus ESC is yet unclear and it may be hypothesized that it is related to the methods used for reprogramming [15]. Furthermore, only a few studies have compared the frequency of genomic rearrangements in iPSC with respect to different methods of reprogramming [16].…”
Section: Introductionmentioning
confidence: 99%